New AMS Radiocarbon Ages from the Preceramic Levels of Coxcatlan Cave, Puebla, Mexico: A Pleistocene Occupation of the Tehuacan Valley?. Issue 3 (September 2021) - Somerville, Andrew D.; Casar, Isabel; Arroyo-Cabrales, Joaquín
Abstract : Archaeological studies at Coxcatlan Cave in the Tehuacan Valley of southern Puebla, Mexico, have been instrumental to the development of the chronology for the region and for our understanding of the origins of food production in the Americas. This article refines the Preceramic chronology of the Tehuacan Valley by presenting 14 new accelerated mass spectrometry (AMS) radiocarbon ages from faunal bone samples uncovered from early depositional levels of the rock shelter. Although bones associated with the El Riego (9893–7838 cal BP), Coxcatlan (7838–6375 cal BP), and Abejas (6375–4545 cal BP) phase zones of the cave yielded ages similar to those of the previously proposed chronology for the region, bones from the Ajuereado phase zones at the base of the cave yielded surprisingly old ages that range from 33, 448 to 28, 279 cal BP, a time prior to the Last Glacial Maximum. Because these early ages are many thousands of years older than current models estimate for the peopling of the Americas, they require reassessments of the artifacts and ecofacts excavated from these early zones.